MiR-539-3p impairs osteogenesis by suppressing Wnt interaction with LRP-6 co-receptor and subsequent inhibition of Akap-3 signaling pathway - Tripathi, Alok; John, Aijaz A.; Kumar, Deepak; Kaushal, Saurabh Kumar; Singh, Devendra Pratap; Husain, Nazim; Sarkar, Jayanta; Singh, Divya (Frontiers in Endocrinology, 2022)
X-linked hypophosphatemia (XLH), an inheritable form of rickets is caused due to mutation in Phex gene. Several factors are linked to the disease’s aetiology, including non-coding RNA molecules (miRNAs), which are key post-transcriptional regulators of gene expression and play a significant role in osteoblast functions. MicroRNAs sequence analysis showed differentially regulated miRNAs in phex silenced osteoblast cells. In this article, we report miR-539-3p, an unidentified novel miRNA, in the functional regulation of osteoblast. MiR-539-3p overexpression impaired osteoblast differentiation. Target prediction algorithm and experimental confirmation by luciferase 3’ UTR reporter assay identified LRP-6 as a direct target of miR-539-3p. Over expression of miR-539-3p in osteoblasts down regulated Wnt/beta catenin signaling components and deteriorated trabecular microarchitecture leading to decreased bone formation in ovariectomized (Ovx) mice. Additionally, biochemical bone resorption markers like CTx and Trap-5b were elevated in serum samples of mimic treated group, while, reverse effect was observed in anti-miR treated animals along with increased bone formation marker P1NP. Moreover, transcriptome analysis with miR-539-3p identified a novel uncharacterized Akap-3 gene in osteoblast cells, knock down of which resulted in downregulation of osteoblast differentiation markers at both transcriptional and translational level. Overall, our study for the first time reported the role of miR-539-3p in osteoblast functions and its downstream Akap-3 signalling in regulation of osteoblastogenesis.